2023
DOI: 10.1007/s00167-023-07558-x
|View full text |Cite
|
Sign up to set email alerts
|

Combined anterior cruciate ligament revision with reconstruction of the antero‐lateral ligament does not improve outcome at 2‐year follow‐up compared to isolated acl revision; a randomized controlled trial

Ole Gade Sørensen,
Peter Faunø,
Lars Konradsen
et al.

Abstract: Purpose It is essential to obtain rotational stability of the knee after anterior cruciate ligament reconstruction (ACL-R) and it is suggested that a supplementary reconstruction of the antero-lateral ligament (ALL-R) may supports this. Theoretically, ALL-R may be particularly advantageous to support revision of failed ACL-Rs. It was hypothesized that ACL revision combined with ALL-R will result in superior outcome compared to isolated ACL revision. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 97 publications
0
2
0
Order By: Relevance
“…These data are not available in the registry. However, the impact of ALL stabilisation in revision ACL surgery has been questioned in a recently published randomised controlled trial found no difference in clinical and subjective outcomes after isolated ACL revision with or without ALL in a cohort of ACL revision patients [12]. Finally, the completeness of the stabilityrelated clinical outcome parameters at the 1-year follow-up was low (28-34%).…”
Section: Discussionmentioning
confidence: 99%
“…These data are not available in the registry. However, the impact of ALL stabilisation in revision ACL surgery has been questioned in a recently published randomised controlled trial found no difference in clinical and subjective outcomes after isolated ACL revision with or without ALL in a cohort of ACL revision patients [12]. Finally, the completeness of the stabilityrelated clinical outcome parameters at the 1-year follow-up was low (28-34%).…”
Section: Discussionmentioning
confidence: 99%
“…The anterolateral ligament (ALL) is a capsular reinforcement located between the Gerdy's tubercle and lateral femoral condyle, which contributes to internal knee rotation stabilisation [45]. However, the effect of ALL reconstruction on internal knee rotation stabilisation has shown diverging results [17,45,47,51].…”
Section: Introductionmentioning
confidence: 99%